Microcirculatory injuries of patients with chronic generalized periodontitis and their correction with EHF-therapy - V. F. Kiritchuk; A. V. Lepilin; I. P. Apalkov; N. L. Yerokina (Бюллетень сибирской медицины)
The aim is the study of EHF-therapy (extremely high frequency therapy) potential for the correction of microcirculatory injuries of patients with chronic generalized periodontitis in postsurgery period: in blood rheological properties and hemostasis system, change of oral fluid ability to coagulation. 42 patients have been examined and treated, including a complex periodontium examination: parodontal recess depth, stomatorrhagia at probing and gum capillary resistance. There have been determined a blood viscosity, erythrocyte aggregation, erythrocyte membrane deformability with rotation viscometer ABR-2; as well as activated partial thromboplastin time, prothrombin time, activity with coagulometer «Sola-Cey 2120» (Byelorussia) using reagents of «Tyekhnologiya-standart» company (Barnaul, Russia). An apparatus «Yavj-1» with wave-length of 5,6 mm with the exposure to biologically active face points (cv-26, cv-27, st-7, st-8) has been used for EHF-therapy. There has been demonstrated that patients with chronic generalized periodontitis had blood rheological and coagulation properties disturbed, that accompanied with the increase of blood viscosity, erythrocyte aggregation, tissue prothrombinase activity and the decrease of blood antithrombin and anticoagulant activity. Patients oral fluid components intensify the disturbances in blood rheological properties due to erythrocyte aggregation increase, and at the same time increase the blood coagulation potential. EHF-therapy recovers the blood rheological properties (its viscosity) more effectively, erythrocyte ability to aggregation and hemostasis system factors in comparison with the traditional treatment.